Four new varieties of Begonia from interspecific hybridization Begonia natunaensis C.W.Lin & C.I.Peng Ã— Begonia puspitae Ardi - HARTUTININGSIH M. SIREGAR (Biodiversitas Journal of Biological Diversity, 2016)
Siregar HM. 2016. Four new varieties of Begonia from interspecific hybridization Begonia natunaensis C.W.Lin & C.I.Peng Ã— Begonia puspitae Ardi. Biodiversitas 17: 776-782. Increased phenotypic diversity of ornamental plants (e.g. Begonia) can often be achieved by hybridization and selection in the F1 generation. This study aimed to produce new F1 varieties which it was hoped would display improved phenotypic characteristics compared to the contributing parents. The study was conducted in the green house of Bogor Botanic Gardens. Two native species of Indonesia, Begonia natunaensis C.W.Lin & C.I.Peng and B. puspitae Ardi, were used as parent plants. The mature F1 seeds were sown and selections were made among the plants produced. The result of the selection were four new accessions of F1 plants (X1, X3, X10, X22). The selected F1 plants were then propagated vegetatively with leaf cuttings. These were named, described and registered at the Center for Plant Variety Protection (PPVTPP). This resulted in the registration of the following F1 cultivars: X1 named Begonia Blirik which is registered as No. 347/PVHP/2015 and is characterized by purplish peltate leaves with bright whitish green veins, and white flowers; X3 named Begonia Fiandani, registered as No. 348/PVHP/2015 and characterized by dark green leaf color, corrugated leaf surface, and pink flowers; X10 named Begonia Green Peltate, registered as No. 345/PVHP/2015 and characterized by large green peltate leaves, and red flowers; and X22 named Begonia Natunapangean, registered as No. 346/PVHP/2015, and characterized by eccentrically shaped, green basifixed leaves, with ovate shape, and cordate leaf base. Thus the new varieties have been registered in PPVTPP, in accordance with legislation in force. These new varieties are beautiful ornamental Begonia hybrids with exotic leaves, which will be developed as commercial ornamental plants. Keywords: Begonia natunaensis, Begonia puspitae, Begonia Blirik, Begonia Green peltate, Begonia Natunapangean, Begonia Fiandani, interspecific hybridization